LEGAL IMPLICATIONS OF THE REGULATION OF THE MINISTER OF HEALTH'S AUTHORITY IN MINISTER OF HEALTH REGULATION NUMBER 3 OF 2025 THAT EXCEEDS THE PRINCIPLE OF ULTRA VIRES - Nina Ayu Wandira; Fatma Ulfatun Najicha (RADJA PUBLIKA, 2026)
This study examines the legal implications of Minister of Health Regulation Number 3 of 2025 in relation to the principles of legal certainty and the hierarchy of laws and regulations in Indonesia. The analysis focuses on provisions regulating professional disciplinary violations, particularly Article 4 paragraph (2), which grants the Minister of Health broad discretion to determine or add categories of disciplinary violations without clear limitations or explicit delegation from higher legal instruments, namely Law Number 17 of 2023 on Health and Government Regulation Number 28 of 2024. Such regulatory construction indicates an exercise of authority that exceeds delegated technical–operational functions and introduces new substantive norms, thereby constituting an ultra vires act within the framework of authority theory and normative hierarchy. Drawing on Hans Kelsen’s theory of the hierarchy of norms, the study argues that the validity of ministerial regulations depends on their conformity with higher norms. Moreover, from Gustav Radbruch’s perspective on legal certainty, norms that confer unlimited authority create ambiguity and unpredictability for medical professionals as subjects of law, undermining the law’s function as a clear and reliable guideline. The study concludes that regulatory provisions exceeding delegated authority pose serious risks to legal certainty and the coherence of the legal system, and therefore require revision to restore normative consistency and protect professional discipline within a rule-of-law framework.